Pengaruh DER dan NPM terhadap Nilai Perusahaan pada Perusahaan Properti dan Real Estate yang terdaftar di BEI - Indah Widyah Ningsih; Deni Malik; Mursidah Nurfadillah; Fenty Fauziah (RJABM (Research Journal of Accounting and Business Management), 2023)
This study aims to identify significant influence between Debt to Equity Ratio (DER) and Net Profit Margin (NPM) on firm value proxied by Price Book Value (PBV) in property and real estate companies listed on the Indonesia Stock Exchange. This study uses a multiple linear regression method with quantitative approach and uses a purposive sampling method with sampling techniques on property and real estate companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The final sample of the study was 39 firm-years. The results of this study indicate that there’s a significant effect of Debt to Equity Ratio (DER) on Firm Value and there’s no significant effect on Net Profit Margin (NPM) on Firm Value. This research was expected to be a reference and material for consideration in making investment decisions for investors, as well reference for  considering company value and efforts to increase company value in order to attract investors to invest their capital for the company. Keywords : DER, NPM dan Firm Value